Is doping-free sport a utopia? - Seiler, S.; Beneke, R.; Halson, S. L.; Impellizzeri, F. M.; Mujika, I.; Pyne, D. B.; Foster, C (International Journal of Sports Physiology and Performance, 2013)
It is discussed weather doping-free sport is possible or not.